Screening for Arabidopsis mutants with altered Ca2+ signal response using aequorin-based Ca2+ reporter system - Shujing Sun; Xiaoyan Zhang; Kong Chen; Xiaohong Zhu; Yang Zhao (STAR Protocols, 2021)
Summary: Environmental stimuli evoke transient increases of the cytosolic Ca2+ level. To identify upstream components of Ca2+ signaling, we have optimized two forward genetic screening systems based on Ca2+ reporter aequorin. AEQsig6 and AEQub plants were used for generating ethyl methanesulfonate (EMS)-mutagenized libraries. The AEQsig6 EMS-mutagenized library was preferably used to screen the mutants with reduced Ca2+ signal response due to its high effectiveness, while the AEQub EMS-mutagenized library was used for screening of the mutants with altered Ca2+ signal response.For complete details on the use and execution of this protocol, please refer to Chen et al. (2020) and Zhu et al. (2013).